Falas oblíquas: O engodo da Palavra em Tutameia (terceiras estórias), de João Guimarães Rosa - Melo, Diana Oliveira de (2011)
This works aims at analyzing the production Tutameia – Terceiras Estórias, by João Guimarães Rosa, from a perspective on the lure of the literary word, and how to weave its intricacies and elaborate writing. The study will be more detailed narratives from three previously chosen, entitled “Hiato”, “João Porém, o criador de perus” and “Antiperipleia”. It is based on the thought of the french writer Maurice Blanchot, we will examine the construction of Rosa’s written on aspects of grounded by issues such as: the impossibility of death in the literary space, the search for the origin of the word as written direction of the instability and the fragmentation of narrative, which leads to an inaccuracy, and lack of order is established in the literary universe, that the writing is submitted, among other things. It is through these considerations that we commented on the speeches in the construction of this writing, in which the regular venue of the word, always willing to establishments credible solutions and speeches looking to stick to the true, is the fictional, which is associated the ludic and the pretence, forces arising from the literary language, attempts to destabilize the truth.